2016
DOI: 10.1161/atvbaha.115.307030
|View full text |Cite
|
Sign up to set email alerts
|

Low-Density Lipoprotein Receptor–Dependent and Low-Density Lipoprotein Receptor–Independent Mechanisms of Cyclosporin A–Induced Dyslipidemia

Abstract: H yperlipidemia is observed in 40% to 60% of organ transplant recipients and has been linked to the use of immunosuppressant agents such as corticosteroids, sirolimus, and cyclosporine A (CsA).1-3 Transplant hyperlipidemia is characterized by high plasma cholesterol and triglyceride levels. Specifically, CsA increases very low-density lipoprotein (VLDL) and low-density lipoprotein (LDL) concentrations and shows variable effects on plasma high-density lipoprotein. Although multiple factors potentially contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 36 publications
(35 reference statements)
0
15
0
1
Order By: Relevance
“…That is to say, the former presented a preventive effect and the latter presented a therapeutic effect. Kockx et al have confirmed that CsA‐induced hyperlipidemia is associated with abnormal serum cholesterol clearance . So CsA may mediate lipid metabolism by down‐regulating the contents of TG in liver, inhibiting the clearance of cholesterol in blood, or both.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…That is to say, the former presented a preventive effect and the latter presented a therapeutic effect. Kockx et al have confirmed that CsA‐induced hyperlipidemia is associated with abnormal serum cholesterol clearance . So CsA may mediate lipid metabolism by down‐regulating the contents of TG in liver, inhibiting the clearance of cholesterol in blood, or both.…”
Section: Discussionmentioning
confidence: 98%
“…Kockx et al have confirmed that CsA-induced hyperlipidemia is associated with abnormal serum cholesterol clearance. (49) So CsA may mediate lipid metabolism by down-regulating the contents of TG in liver, inhibiting the clearance of cholesterol in blood, or both. Considering the wide pharmacological effects of CsA, (50) it is necessary to eliminate the possibility that decreased hepatic TG accumulation was derived from secondary effects.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies investigating the potential mechanisms underlying the pathogenesis of new-onset diabetes following tacrolimus-based treatments had focused on insulin-resistance [ 8 , 10 , 33 37 ]. Alterations in peripheral insulin-signaling have been also reported in response to other immunomodulators, including rapamycin, cyclosporine A, and steroids [ 38 42 ]. In fact, ultrastructural analysis has revealed that cyclosporine A causes mitochondrial dysmorphology in renal allograft biopsies [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Both sirolimus and everolimus have been associated with the development of severe HTG (106,107). These agents increase APOC3 levels and inhibit LPL (108,109).…”
Section: Immunosuppressive Agentsmentioning
confidence: 99%